Disproportionality in the attainment of pupils with special educational needs at the end of primary school in England. (12th October 2022) - Demie, Feyisa
Abstract : This research article aims to examine disproportionality in the attainment of pupils with special educational needs at the end of primary education. The sample consisted of 3, 025 pupils who completed Key Stage 2 in one LA in London. Two methodological approaches were used in the data collection. The background data related to special educational needs were collected as part of the January school census and this was then matched at the pupil level to their Key Stage 2 results collected by the Department for Education for all state‐educated pupils in England at end of the summer term. The data were then analyzed further using descriptive statistics. The findings of the analysis of Key Stage 2 results show that pupils with special educational needs in England are much less likely to meet the expected standard, raising key concerns for policymakers and teachers. A number of factors were identified, including pupils' type of need, gender, socio‐economic status, ethnic background and exclusions rate. The data show that some ethnic minorities are more likely to be identified with some types of special educational need compared to White British pupils. Policy implications for tackling disproportionality in special educational needs and further research are discussed in the concluding section.